Teachers in the Loop: Integrating Computational Thinking and Mathematics to Build Early Place Value Understanding - Mai Dahshan; Terrie Galanti (MDPI AG, 2024)
With increasing attention on the potential overlap between computational thinking (CT) and mathematical reasoning, STEM education researchers seek to understand how integrating CT and mathematics can deepen student learning across disciplines. Although there are various professional development programs that introduce teachers to CT concepts and strategies for curriculum integration, limited research exists on how teachers might apply this knowledge to create math + CT activities for use with their students. Additionally, the majority of research on CT integration through programming has focused on upper elementary grades, leaving the early grades (K-2) relatively unexplored. This qualitative exploratory study aims to examine how teachers in a graduate STEM education program collaborated with university STEM faculty to explore and critique a set of integrated math + CT block-based programming activities designed to build place value conceptual understanding. In-service elementary teachers enrolled in an online graduate CT course for educators (n = 13) explored these activities as learners and drew on their experiences as classroom teachers to offer feedback for program redesign. A sequence of deductive pattern coding and inductive holistic coding of course transcripts, collaborative problem-solving slides, and individual teacher reflections provided insights into how teachers were able to establish connections between their mathematical knowledge related to teaching place value and their emerging understanding of CT concepts, such as abstraction, algorithms, decomposition, and debugging. Implications for the design of professional development for elementary teachers on integrating CT and mathematics are offered.